vol 2 no 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: Konsep Ekonomi Kerakyatan dalam Meningkatkan Kesejahteraan Masyarakat - muna, rifatul (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2024)
The concept of people's economy is one of the instruments of the economic system in Indonesia. The birth of this concept was motivated by the economic downturn at that time. During the 1997 monetary crisis in Indonesia, many economic collapses occurred. However, the concept of people's economics is still able to stand tall with the principle of mutual cooperation in developing the economy. Likewise, the concept of sharia cooperatives is currently continuing to increase by prioritizing the concept of family. The library research research approach is used to make it easier to describe research results. This is obtained through books, journals, articles and other documents relevant to the discussion theme. The results of this research show that the concept of people's economics is able to provide solutions in the development of sharia cooperatives in Indonesia. By prioritizing the principle of mutual help (at-ta'awun), people will have more confidence in transactions in sharia cooperatives. There are at least three basic components of a people's economy in developing a sharia economy, namely, the principle of togetherness, power belonging to the people and prioritizing the people at large.